Changes in Reverse Transcription Polymerase Chain Reaction–positive Severe Acute Respiratory Syndrome Coronavirus 2 Rates in Adults and Children According to the Epidemic Stages. Issue 11 (November 2020) - Levy, Corinne; Basmaci, Romain; Bensaid, Philippe; Bru, Cécile Bost; Coinde, Edeline; Dessioux, Emmanuelle; Fournial, Cécile; Gashignard, Jean; Haas, Hervé; Hentgen, Véronique; Huet, Frédéric; Lalande, Muriel; et al.
Abstract : From March 2, 2020, to April 26, 2020, 52, 588 reverse transcription polymerase chain reaction (RT-PCR) tests for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were performed in France, 6490 in children and 46, 098 in adults. The rate of RT-PCR–positive SARS-CoV-2 tests for children (5.9%) was always less than that for adults (20.3%) but vary according to the epidemic stage. The risk ratio of RT-PCR–positive SARS-CoV-2 tests for adults compared with children was 3.5 (95% confidence interval: 3.2–3.9) for the whole study period. Abstract : Supplemental Digital Content is available in the text.